Synthesis and characterization of polymer electrolyte membrane containing methylisatin moiety by polyhydroalkylation for fuel cell. (8th March 2018) - Ryu, Taewook; Jang, Hohyoun; Ahmed, Faiz; Lopa, Nasrin Siraj; Yang, Hanmo; Yoon, Sujin; Choi, Inhwan; Kim, Whangi
Abstract: High molecular weight polymer containing N -methylisatin was synthesized by superacid-catalyzed polyhydroxyalkylation reactions. Their functionality with sulfonic acid groups and the measurement of apposite parameters for proton exchange membranes (PEMs) were described. Sulfonic acid groups were introduced into the polymer through sulfonation reaction with chlorosulfonic acid. The membranes were casted from the solution of sulfonated polymer in dimethylsulfoxide (DMSO). The structural properties of the synthesized polymers were investigated by 1 H NMR spectroscopy. The membranes were studied by thermogravimetric analysis (TGA), ion exchange capacity (IEC), water uptake, dimensional stability and proton conductivity assessment. Different levels of sulfonation and ion exchange were tested; the resulting membranes exhibited high proton conductivities of up to 88.63 mS/cm. The sulfonated membranes showed good dimensional stability owing to having all carbon-carbon linkages on polymers' backbone. Graphical abstract: A polymer series of poly(phenylene) containing 1-methylisatin moiety without ether linkage was synthesized by polyhydroxyalkylation polymerization and sulfonation reaction of poly(phenylene) was controlled by chlorosulfonic acid mole ratio. Compared with Nafion 211 ® membrane, these SPPs showed logical IECs from 1.55 to 2.48 meq/g, water uptake from 31.8 to 62.5 %, and high thermal stability. The proton conductivity is still lower than that of Nafion 211 ® like typical hydrocarbon membranes' performance. Moreover, power density was mearsured from 0.50 to 0.57. The results show that the proton conductivity and membranes swelling significantly depend on the chemical structure of monomer and polymer matrix. These properties are momentous in PEMFC applications and make the membranes attractive for PEM materials. Highlights: The sulfonated polyphenylenes containing isatin structure were synthesized. The degree of sulfonation was controlled by concentration of chlorosulfuric acid. Increasing sulfonation level increases proton conductivity. Membranes have good performances, particularly chemical stability.